Intravenous propafenone for conversion of atrial fibrillation or flutter to sinus rhythm: A randomized, placebo-controlled, crossover study - TOKAY TARHAN, SENA (SAGE Publications Ltd, 1997)
Background: Propafenone has been claimed to be effective in converting atrial fibrillation and flutter to sinus rhythm; however, controlled clinical trials have reported variable results, and data about the safety of propafenone in the setting of heart failure are lacking. The aim of the present study was to evaluate the efficacy and safety of intravenous propafenone in converting atrial fibrillation and flutter to sinus rhythm. Methods: Sixty patients with acute (< 72 h) or chronic atrial fibrillation or flutter were included in a randomized, placebo-controlled, conditional cross- over study. Twenty eight patients, of whom 12 were in New York Heart Association class III and IV, had heart failure. Patients received intravenous propafenone (2 mg/kg in 10 minutes) and placebo subsequently at 1 hour intervals if sinus rhythm was not achieved. The patients' rhythms were continuously monitored for 1 hour and a 12-lead electrocardiogram, a 1- minute continuous rhythm strip and vital signs were recorded at baseline and at 15, 30, 45, and 60 minutes after the administration of each drug. Results: Twenty of the 59 patients (34%) treated with propafenone converted to sinus rhythm, while only 4 of the 50 patients (8%) treated with placebo converted (P < .001). Propafenone was more effective in patients with acute (< 72 h) atrial fibrillation (64.5%). The conversion rate with propafenone was not significantly different from placebo in patients with atrial flutter and chronic atrial fibrillation (> 72 h). Propafenone significantly decreased (P < .005 vs placebo) mean ventricular rate in nonresponders with a baseline heart rate of more than 100 beats/min. No clinically significant adverse effect occurred. Conclusions: We conclude that intravenous propafenone treatment is effective for converting acute atrial fibrillation; however, it seems unlikely to be beneficial in atrial flutter and chronic atrial fibrillation. Propafenone decreases ventricular rate in nonresponders, and a single dose of propafenone is relatively safe even in moderate-to-severe heart failure.
Keywords: Atrial fibrillation; Propafenone